Competitiveness of Indonesian Shrimp Export to the United States - Lim Sanny; Darma Kusuma; Martinus Evan Willyanto (Binus Business Review, 2021)
Agricultural sector in Indonesia contributes greatly to employment, foreign exchange earners, and economic growth. In the export sector, shrimp commodities have the largest portion and become Indonesia's leading commodities. However, Â Indonesia still cannot become a leader in the world's largest shrimp exporter and only occupies the fourth position of the world's shrimp exporter. There were two goals in the research. First, it was to determine the position of the competitiveness of Indonesian shrimp commodity exports compared to other exporting countries in the United States market. Second, it determined the factors that affected the competitiveness of shrimp exports commodity and made business strategy recommendations for Indonesian shrimp commodities. The research used panel data with a cross-section of seven countries and time series from 2001 to 2017. The result shows that Indonesia has a competitive advantage in the United States market. However, Indonesia must be wary of Ecuador with a higher Revealed Comparative Advantage (RCA) Value and India, the lead exporter in the United States Market. The factors that affect the competitiveness of shrimp exports are Gross Domestic Product (GDP), population, economic distance, and exchange rate of shrimp exporting countries against the US Dollar. Last, the right business strategy for Indonesia is to perform market penetration, market development, and product development strategies.